Integrated Analytical Hierarchy Process and Decision Tree Approach for Strategic Supplier Selection of Electric Motors in Cement Manufacturing: A Multi-Criteria Decision Framework - Safriza Naufal Amzad; Tajus Syabrina; Dini Syahriza Fahlevi; Aulia Nur (Jurnal Nasional Komputasi dan Teknologi Informasi, 2026)
Abstract - The selection of suppliers for critical manufacturing components represents a highly strategic decision with direct implications for operational continuity and financial stability in heavy industries. In cement manufacturing, electric motors driving cooler fan systems are indispensable for maintaining the stability of the clinker cooling process, and any failure without an immediate replacement can trigger severe production stoppages and substantial financial losses. Despite the growing sophistication of procurement methodologies, a persistent gap exists in frameworks that simultaneously address deterministic quality criteria and probabilistic financial risks within a single evaluation model. This study develops and applies an integrated multi-criteria decision-making (MCDM) framework that combines the Analytical Hierarchy Process (AHP) for criteria weighting and supplier evaluation with Decision Tree analysis for risk-adjusted financial modeling. The research evaluates four pre-qualified supplier alternatives against five criteria: Price, Quality, Delivery Time, Warranty, and Technical Support. The AHP analysis reveals that Quality is the most critical criterion (weight = 0.55), followed by Delivery Time (0.25) and Price (0.20), with a Consistency Ratio below 0.10 confirming the validity of expert judgments. The AHP evaluation ranks Supplier C, an Original Equipment Manufacturer (OEM), as the top choice with a composite score of 0.42 due to superior product reliability. Conversely, the Decision Tree analysis, which incorporates delivery delay probabilities and downtime cost scenarios through Expected Monetary Value (EMV) calculations, identifies Supplier B as the optimal alternative owing to the best balance between procurement cost and delivery risk. The divergence between results underscores the complementary nature of the integrated approach. Managerial recommendations include pursuing negotiations with Supplier C for accelerated delivery while retaining Supplier B as a strategic contingency. This study contributes a novel dual-lens procurement framework applicable to critical spare parts procurement across heavy manufacturing industries. Keywords: Supplier Selection; Analytic Hierarchy Process; Decision Tree; Expected Monetary Value; Cement Manufacturing; Multi-Criteria Decision Making; Strategic Procurement;   Abstrak - Pemilihan pemasok untuk komponen manufaktur kritis merupakan keputusan yang sangat strategis dengan implikasi langsung terhadap kelangsungan operasional dan stabilitas keuangan di industri berat. Dalam industri semen, motor listrik yang menggerakkan sistem kipas pendingin sangat penting untuk menjaga stabilitas proses pendinginan klinker, dan setiap kegagalan yang tidak segera diganti dapat memicu penghentian produksi yang parah serta kerugian finansial yang signifikan. Meskipun metodologi pengadaan semakin canggih, masih terdapat kesenjangan yang terus berlanjut dalam kerangka kerja yang secara bersamaan menangani kriteria kualitas deterministik dan risiko keuangan probabilistik dalam satu model evaluasi. Penelitian ini mengembangkan dan menerapkan kerangka kerja pengambilan keputusan multi-kriteria (MCDM) terintegrasi yang menggabungkan Proses Hirarki Analitis (AHP) untuk penentuan bobot kriteria dan evaluasi pemasok dengan analisis Pohon Keputusan untuk pemodelan keuangan yang disesuaikan dengan risiko. Penelitian ini mengevaluasi empat alternatif pemasok yang telah lolos prakualifikasi berdasarkan lima kriteria: Harga, Kualitas, Waktu Pengiriman, Garansi, dan Dukungan Teknis. Analisis AHP menunjukkan bahwa Kualitas merupakan kriteria paling kritis (bobot = 0,55), diikuti oleh Waktu Pengiriman (0,25) dan Harga (0,20), dengan Rasio Konsistensi di bawah 0,10 yang mengonfirmasi validitas penilaian para ahli. Evaluasi AHP menempatkan Pemasok C, sebuah Produsen Peralatan Asli (OEM), sebagai pilihan teratas dengan skor gabungan sebesar 0,42 berkat keandalan produk yang unggul. Sebaliknya, analisis Pohon Keputusan, yang memperhitungkan probabilitas keterlambatan pengiriman dan skenario biaya downtime melalui perhitungan Nilai Moneter yang Diharapkan (EMV), mengidentifikasi Pemasok B sebagai alternatif optimal karena keseimbangan terbaik antara biaya pengadaan dan risiko pengiriman. Perbedaan antara hasil tersebut menggarisbawahi sifat saling melengkapi dari pendekatan terintegrasi ini. Rekomendasi manajerial mencakup upaya negosiasi dengan Pemasok C untuk mempercepat pengiriman sambil tetap mempertahankan Pemasok B sebagai cadangan strategis. Studi ini menyumbangkan kerangka kerja pengadaan dual-lens yang inovatif yang dapat diterapkan pada pengadaan suku cadang kritis di seluruh industri manufaktur berat. Kata kunci: Pemilihan Pemasok; Proses Hirarki Analitik; Pohon Keputusan; Nilai Moneter yang Diharapkan; Manufaktur Semen; Pengambilan Keputusan Multikriteria; Pengadaan Strategis;